Inhibition of Ubiquitin Specific Protease 1 Sensitizes Colorectal Cancer Cells to DNA-Damaging Chemotherapeutics - Xu, Xin; Li, Shaoyan; Cui, Ximao; Han, Kunkun; Wang, Jun; Hou, Xiaodan; Cui, Long; He, Songbing; Xiao, Jiecheng; Yang, Yili (Frontiers in Oncology, 2019)
Mutations and altered expression of deubiquitinating enzymes (DUBs) have been found associated with many human diseases including cancers. In this study, Ubiquitin specific protease 1 (USP1) expression was found significantly increased in some colorectal cancers (CRC). The elevated USP1 level was associated with short overall survival of patients and with advanced stages of cancers. In cultured CRC cells, knockdown of USP1 induced growth arrest at G2/M of cell cycle and reduced the expression of anti-apoptotic proteins Bcl-2 and Mcl-1. Its knockdown also led to reduction of DNA-repair related substrates FANCD2 and ID1. Further investigations found that small molecular inhibitor of USP1 ML323 sensitized CRC cells to DNA-targeting chemotherapeutics, including doxorubicin, TOPI/II inhibitors, and PARP inhibitor, but not to 5-Fu. These results indicate that USP1 plays a critical in colorectal cancer cell survival and is a promising target for anti-colorectal cancer chemotherapy. Targeting USP1 may represent an effective strategy to regulate the DNA-repairing system.